(3HjGf NWGA ef CNWC Ydi GdTGaYis - (3CHh HcQ CMeO Hf GdMSjf Hf Ydj GdNQGSGfj GdTGaYj, GdHjgbj,J (B458 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf caGA Mbg hGdUdGI Ydi QShdg eMeO NjQ Ndbg hYdi GdWGgQjf ef Bdg s
(3BNQgG (B:s
(3hGddg JYGdi jQMefG hEjGg ade jJQc dYGjH eYeQkG hHGddg GdJhajb hGdYUeI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B206s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B261s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs